Characterising Post-mortem Bacterial Translocation Under Clinical Conditions Using 16S rRNA Gene Sequencing in Two Animal Models - Gates, Lily; Klein, Nigel J.; Sebire, Neil J.; Alber, Dagmar G. (Frontiers in Microbiology, 2021)
Aims Interpretation of post mortem microbiology results remains a difficult task, particularly in cases of sudden and unexpected death in infancy and childhood where clinical history and other findings remain unclear. This is due to possible generation of false-positive results. This study aims to assess post mortem bacterial translocation from highly colonised sites to extra-intestinal tissues. Methods Using 16S rRNA gene sequencing in two animal models (mouse and piglet), bacterial presence was investigated in multiple tissues including the heart, lung and liver over a two-week period post mortem. In addition, community succession in highly colonised sites such as the nasal and rectal cavities was measured. Results There were little changes in the gut microbiome in the mice and piglets over the two-week period. In the mouse model only 4/45 tissues were successfully sequenced and analysed with low sequencing reads. The piglet model had 29/45 positive tissues but only 10/29 and 8/29 were identified in the rectal and nasal cavities respectively. There was no correlation between tissue type or day post-mortem with positive tissues. Conclusions No evidence was found for significant and consistent PM bacterial translocation in the mouse model. Although bacteria were detected amongst some tissues in the piglet model, we did not find significant and consistent evidence for PM bacterial translocation from the GI tract or nasal cavity. These data do not support the concept of significant PM translocation as part of the normal PM process.